Conductive polymer-coated bismuth oxychloride positive electrode material for chloride ion batteries and preparation method thereof

By covering the conductive polymer on the BiOCl positive electrode material, the problems of poor conductivity and volume changes of BiOCl positive electrode material are solved, and its electrochemical performance is significantly improved, especially in the application in chloride ion batteries.

CN116969507BActive Publication Date: 2025-04-25NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310492828.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-04-25
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The poor conductivity of BiOCl positive electrode materials and volume changes during charging and discharging limit their electrochemical properties, especially in chloride ion batteries.

Method used

By ultrasonic and stirring the BiOCl with polymer monomer and surfactant in NaCl solution, ammonium persulfate solution was added dropwise to polymerize to form a conductive polymer-coated BiOCl positive electrode material.

Benefits of technology

This method significantly improves the conductivity of BiOCl positive electrode material, effectively alleviates the volume changes of the electrode material during the cycle, improves the electrochemical performance, the first discharge capacity reaches 249 mAh/g, and still has a capacity of 89 mAh/g after 30 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116969507B_ABST
    Figure CN116969507B_ABST
Patent Text Reader

Abstract

The present invention provides a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery and a preparation method thereof. Under neutral conditions, sodium chloride is used as a dopant, and a surfactant is added in the reaction to induce uniform growth of a polymer on the surface of BiOCl and avoid loss of BiOCl. The conductive polymer-coated bismuth oxychloride positive electrode material is successfully prepared. The obtained positive electrode material has good conductivity, and the coating layer can effectively alleviate the volume change of the electrode material during the cycle process, thereby improving the electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, in particular to the technology of positive electrode materials for chloride ion batteries, and in particular to a conductive polymer-coated bismuth oxychloride positive electrode material for chloride ion batteries and a preparation method thereof. Background Art

[0002] In recent years, there have been numerous reports on positive electrode materials for chloride ion batteries. Metal chloride oxide positive electrode materials are one of the hot topics of research, including FeOCl, BiOCl, Sb4O5Cl2, VOCl, VOCl2 and WOCl4. The metal cations in metal chloride oxides can be firmly bound by the oxygen ions of strong Lewis bases, so no desolvation reaction similar to that of metal chlorides in electrolytes will occur. Therefore, chloride ion batteries with metal chloride oxides as positive electrodes have the ability to cycle for a long time. Most metal chloride oxides exist in the form of a layered structure. Chloride ions exist between the layers and have a weak binding force with metal ions, which is conducive to the gain and loss of chloride ions, thereby realizing the conversion between electrical energy and chemical energy. However, poor conductivity and volume changes during charging and discharging are the main reasons affecting the electrochemical performance of metal chloride oxide positive electrodes. Therefore, it is very necessary to modify the metal chloride oxide positive electrode.

[0003] Since XY Zhao et al. first proposed the use of two metal oxychlorides (FeOCl and BiOCl) as positive electrode materials for chloride ion batteries in Metal Oxychlorides as Cathode Materials for Chloride Ion Batteries in 2013, FeOCl materials have attracted the attention of researchers. Researchers have adopted many methods to modify FeOCl positive electrode materials and achieved certain results. XY Zhao et al. mechanically ball-milled FeOCl with different carbon materials (carbon nanotubes, carbon black, graphene nanoplates) in Carbon incorporation effects and reaction mechanism of FeOCl cathode materials for chloride ion batteries in order to improve its electronic conductivity and buffer the volume change during charge and discharge. The FeOCl / graphene composite positive electrode has an initial discharge capacity of 184 mAh / g at a current density of 10 mA / g. However, mechanical ball milling leads to the decomposition of FeOCl and insufficient contact with carbon materials, resulting in poor cycle stability of the composite material, and the post-discharge capacity decays to 50 mAh / g after 50 cycles. Later, TT Yu et al. confined FeOCl materials inside porous carbon (CMK-3) in Nanoconfined Iron Oxychloride Material as a High-Performance Cathode for Rechargeable Chloride Ion Batteries, greatly improving the electrochemical performance of FeOCl cathode. The maximum and 30 cycle capacities of the composite material at a current density of 10 mA / g were 202 and 162 mAh / g, respectively. However, the composite method is relatively complicated, and a large part of FeOCl is not confined inside the porous carbon but exposed outside. Later, RJ Yang et al. coated a layer of polypyrrole material on the outside of FeOCl by a simple gas phase polymerization method in Polypyrrole-coated iron oxychloride cathode material with improved cycling stability for chloride ion batteries. The maximum discharge capacity of the composite cathode at a current density of 10 mA / g can reach 187 mAh / g, and the capacity remains at 155 mAh / g after 30 cycles.

[0004] However, there has been no research on the modification of BiOCl cathode materials so far. Although the theoretical capacity of BiOCl cathode is lower than that of FeOCl cathode, it also has its own unique advantages. In addition, BiOCl has a stable structure and is insensitive to water and air, so the conditions for its modification are not as harsh as those for FeOCl. The reported discharge capacity of pure BiOCl is 60 mAh / g, which is only 59% of the theoretical capacity (103 mAh / g). It can be seen that there is still a lot of room for improvement in this cathode material. The main problems facing BiOCl cathode are its poor conductivity and volume changes during charging and discharging. Summary of the invention

[0005] One aspect of the present invention relates to a method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery, comprising the following steps:

[0006] Step 1, dissolving ammonium persulfate in a NaCl solution to obtain a first mixed solution;

[0007] Adding BiOCl, polymer monomers and surfactants into a NaCl solution, and ultrasonicating and stirring to obtain a second mixed solution;

[0008] Step 2, adding the first mixed solution dropwise into the second mixed solution, and stirring the mixture at a desired temperature to react, to obtain a third mixed solution;

[0009] Step 3: Filter the third mixed solution, and wash and dry the obtained solid to obtain a BiOCl@conductive polymer composite material.

[0010] In an optional embodiment, the mass ratio of BiOCl to surfactant is 1:(1-2).

[0011] In an optional embodiment, the ratio of BiOCl to NaCl solution is 1 g:(100~200 mL).

[0012] In an optional embodiment, the molar ratio of the polymer monomer to ammonium persulfate is 1:(1-2).

[0013] In an optional embodiment, the concentration of the NaCl solution is 0.1-0.5 mol / L, wherein the solvent of the NaCl solution is a mixed solvent of a solvent capable of dissolving the corresponding polymer monomer and deionized water.

[0014] In an optional embodiment, in step 1, ultrasonic treatment is performed at a temperature of 0-5°C for 1-2 h, followed by stirring for 1-2 h.

[0015] In an optional embodiment, in step 2, the first mixed solution is added dropwise to the second mixed solution, and stirred at a temperature of 0-5° C. for more than 24 h to obtain a third mixed solution.

[0016] In an optional embodiment, the polymer monomer is one of pyrrole, aniline, diphenylamine, and triphenylamine indole.

[0017] In an optional embodiment, the surfactant is a mixture of one or more of sodium dodecylbenzene sulfonate, sodium benzene sulfonate, sodium p-toluene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyethylene glycol, and polyvinyl alcohol.

[0018] Another aspect of the present invention relates to a bismuth oxychloride positive electrode material coated with a conductive polymer prepared according to the aforementioned method.

[0019] It can be seen from the above technical solutions of the present invention that the present invention successfully modifies the BiOCl chloride ion battery positive electrode material to obtain a conductive polymer-coated BiOCl positive electrode material. The polymer-coated BiOCl positive electrode has good conductivity. At the same time, the coating layer can effectively alleviate the volume change of the electrode material during the cycle, thereby improving the electrochemical performance. It exhibits a higher discharge capacity in the chloride ion battery, with an initial discharge capacity of 249 mAh / g, and a capacity of 89 mAh / g after 30 cycles.

[0020] The polymerization reaction of the present invention is completed under neutral conditions, and sodium chloride is used as a dopant, which effectively avoids the loss of BiOCl while taking into account the conductivity of the material.

[0021] In the present invention, a surfactant is added during the polymerization process to prevent BiOCl particles from agglomerating and induce the polymer to grow uniformly on the surface of BiOCl. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the X-ray diffraction pattern of the BiOCl@polypyrrole composite material in the example of the present invention.

[0023] Figure 2 is a field emission scanning electron microscope image of the BiOCl@polypyrrole composite material in an example of the present invention.

[0024] Figure 3 yes Figure 2 The corresponding energy spectrum element mapping image.

[0025] Figure 4 : is the cycle stability curve of BiOCl@polypyrrole in the example of the present invention, wherein the ordinate is the discharge capacity (mAh / g), the abscissa is the number of cycles (n), and the current density is 10 mA / g. DETAILED DESCRIPTION

[0026] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0027] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0028] The conductive polymer-coated BiOCl reported so far is mainly used in photocatalysis. For example, polyaniline is coated on the surface of BiOCl using FeCl3 as an oxidant. However, since BiOCl decomposes in an acid solution, this method will cause BiOCl loss. The loss of BiOCl will lead to waste, and it will also consume the amount of FeCl3 oxidant or dopant and affect the coating effect. Thirdly, the reduction of BiOCl will lead to a corresponding increase in the amount of polymer, resulting in an overly thick coating layer, which will increase the internal resistance of the battery. If there is an excess of acid, it may even cause all BiOCl to be dissolved.

[0029] This shows that the current method is not suitable for application in battery energy storage.

[0030] Therefore, the present invention provides a new method for coating BiOCl with a conductive polymer, successfully prepares a modified BiOCl positive electrode material for application in battery energy storage, solves the problem of poor conductivity of BiOCl and volume change during charging and discharging, and improves the electrochemical performance of the BiOCl positive electrode.

[0031] In an exemplary embodiment of the present invention, a method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery is provided, comprising the following steps:

[0032] Step 1, dissolving ammonium persulfate in a NaCl solution to obtain a first mixed solution;

[0033] Adding BiOCl, polymer monomers and surfactants into a NaCl solution, and ultrasonicating and stirring to obtain a second mixed solution;

[0034] Step 2, adding the first mixed solution dropwise into the second mixed solution, and stirring the mixture at a desired temperature to react, to obtain a third mixed solution;

[0035] Step 3: Filter the third mixed solution, and wash and dry the obtained solid to obtain a BiOCl@conductive polymer composite material.

[0036] In an optional embodiment, the mass ratio of BiOCl to surfactant is 1:(1-2).

[0037] In an optional embodiment, the ratio of BiOCl to NaCl solution is 1 g:(100~200 mL).

[0038] In an optional embodiment, the molar ratio of the polymer monomer to ammonium persulfate is 1:(1-2).

[0039] In an optional embodiment, the concentration of the NaCl solution is 0.1~0.5 mol / L, wherein the solvent of the NaCl solution is a mixed solvent of a solvent capable of dissolving the corresponding polymer monomer and deionized water; the ratio of the solvent capable of dissolving the corresponding polymer monomer and deionized water is preferably 1:1. It can be understood that the ratio between the two can be adjusted according to actual needs, with the purpose of dissolving ammonium persulfate, polymer monomers, and surfactants.

[0040] In an optional embodiment, in step 1, ultrasonic treatment is performed at a temperature of 0-5°C for 1-2 h, followed by stirring for 1-2 h.

[0041] In an optional embodiment, in step 2, the first mixed solution is added dropwise to the second mixed solution, and stirred at a temperature of 0-5° C. for more than 24 h to obtain a third mixed solution.

[0042] In an optional embodiment, the polymer monomer is one of pyrrole, aniline, diphenylamine, and triphenylamine indole.

[0043] In an optional embodiment, the surfactant is a mixture of one or more of sodium dodecylbenzene sulfonate, sodium benzene sulfonate, sodium p-toluene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyethylene glycol, and polyvinyl alcohol.

[0044] When the surfactant is a mixture of multiple substances, the ratio between the substances can be any ratio and is not further limited here.

[0045] In an optional embodiment, in step 3, the obtained solid is washed with deionized water and ethanol, and vacuum dried at 50-80° C. for 10-20 h to obtain a BiOCl@conductive polymer composite material.

[0046] In another exemplary embodiment of the present invention, a conductive polymer-coated bismuth oxychloride positive electrode material prepared according to the aforementioned method is also provided. The conductive polymer-coated bismuth oxychloride positive electrode material is applied as an active material to the positive electrode of a chloride ion battery. The application results show that the conductive polymer coating layer can effectively buffer the volume expansion of BiOCl during the charge and discharge process and improve the conductivity of BiOCl.

[0047] The following will combine specific examples and experiments to conduct exemplary experiments and comparisons on the preparation of the above-mentioned positive electrode materials and their effects. Of course, the embodiments of the present invention are not limited to these.

[0048] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments can be obtained from commercial sources unless otherwise specified.

[0049] Example 1

[0050] 1 g BiOCl, 1 g sodium dodecylbenzene sulfonate and 0.1 mL pyrrole were added to 100 mL NaCl solution (0.2 mol / L), ultrasonicated at 0 °C for 2 h, and then stirred for 1 h. This solution was recorded as solution A.

[0051] Dissolve 0.34 g of ammonium persulfate in 10 mL of NaCl solution (0.2 mol / L), referred to as solution B.

[0052] Under stirring conditions at 0 °C, B was added dropwise to solution A, and then stirring was continued at 0 °C for 48 h. After the reaction was completed, the mixed solution was filtered, and the obtained solid was washed with water and ethanol, and vacuum dried at 80 °C for 24 h to obtain a BiOCl@polypyrrole composite material.

[0053] Example 2

[0054] 1 g BiOCl, 1 g sodium dodecylbenzene sulfonate and 0.1 mL aniline were added to 100 mL NaCl solution (0.2 mol / L), ultrasonicated at 0 °C for 2 h, and then stirred for 1 h. This solution was recorded as solution A.

[0055] Dissolve 0.34 g of ammonium persulfate in 10 mL of NaCl solution (0.2 mol / L), referred to as solution B.

[0056] Under stirring conditions at 0 °C, B was added dropwise to solution A, and then stirring was continued at 0 °C for 48 h. After the reaction was completed, the mixed solution was filtered, and the obtained solid was washed with water and ethanol, and vacuum dried at 80 °C for 24 h to obtain a BiOCl@polyaniline composite material.

[0057] Example 3

[0058] 1 g BiOCl, 1 g sodium benzenesulfonate and 0.2 mL diphenylamine were added to 100 mL of a mixed solution of NaCl water and ethanol in equal proportions (0.2 mol / L), ultrasonicated at 0 °C for 2 h, and then stirred for 1 h. This solution was recorded as solution A.

[0059] Dissolve 0.68 g of ammonium persulfate in 10 mL of NaCl solution (0.2 mol / L), referred to as solution B.

[0060] Under stirring conditions at 0 °C, B was added dropwise to solution A, and then stirring was continued at 0 °C for 48 h. After the reaction was completed, the mixed solution was filtered, and the obtained solid was washed with water and ethanol, and vacuum dried at 80 °C for 24 h to obtain a BiOCl@polydiphenylamine composite material.

[0061] Example 4

[0062] 1 g BiOCl, 1 g sodium benzenesulfonate and 0.15 mL indole were added to 100 mL of a mixed solution of NaCl water and ethanol in equal proportions (0.2 mol / L), ultrasonicated at 0 °C for 2 h, and then stirred for 1 h. This solution was recorded as solution A.

[0063] Dissolve 0.51 g of ammonium persulfate in 10 mL of NaCl solution (0.2 mol / L), referred to as solution B.

[0064] Under stirring conditions at 0 °C, B was added dropwise to solution A, and then stirring was continued at 0 °C for 48 h. After the reaction was completed, the mixed solution was filtered, and the obtained solid was washed with water and ethanol, and vacuum dried at 80 °C for 24 h to obtain the BiOCl@polyindole composite material.

[0065] Example 5

[0066] 1 g BiOCl, 0.5 g sodium benzenesulfonate, 0.5 g sodium p-toluenesulfonate, 0.1 mL diphenylamine and 0.1 mL indole were added to 100 mL of a mixed solution of NaCl water and ethanol in equal proportions (0.2 mol / L), ultrasonicated at 0 °C for 2 h, and then stirred for 1 h. This solution was recorded as solution A.

[0067] Dissolve 0.68 g of ammonium persulfate in 10 mL of NaCl solution (0.2 mol / L), referred to as solution B.

[0068] Under stirring conditions at 0 °C, B was added dropwise to solution A, and then stirring was continued at 0 °C for 48 h. After the reaction was completed, the mixed solution was filtered, and the obtained solid was washed with water and ethanol, and vacuum dried at 80 °C for 24 h to obtain the BiOCl@diphenylamine indole copolymer composite material.

[0069] X-ray diffraction analysis

[0070] The prepared BiOCl@polypyrrole composite material was subjected to X-ray diffraction analysis. Figure 1 shown.

[0071] It can be seen from the figure that the diffraction peaks of the composite material are all related to the tetragonal crystal structure, and the space group is P4 / nmm The results show that the BiOCl phase is well preserved after coating. A very weak broad peak region can be observed in the range of 20-30°, indicating that amorphous polypyrrole exists in addition to BiOCl.

[0072] Field Emission Scanning Electron Microscope

[0073] The prepared BiOCl@polypyrrole composite material was subjected to X-ray diffraction analysis. Figure 2 shown.

[0074] It can be observed from the figure that BiOCl presents a nanosheet morphology with a size of 200~500 nm. Through the corresponding energy spectrum element mapping image ( Figure 3 ) The uniformly distributed Bi, Cl, and N elements can be seen, indicating that polypyrrole is uniformly distributed on the BiOCl nanosheets.

[0075] The above tests prove that the present invention successfully prepares the BiOCl@conductive polymer composite material.

[0076] Electrochemical performance

[0077] The electrochemical properties of the prepared BiOCl@polypyrrole composite material were further measured according to the following method:

[0078] First, 0.1 g of PVDF was dissolved in NMP, and then 0.6 g of the BiOCl@polypyrrole composite material prepared in Example 1 and 0.3 g of the conductive additive carbon black were ground and added to the solution. After being fully stirred into a paste, the resulting slurry was coated on carbon paper and then vacuum dried at 80 °C for 24 h. The dried film was made into a positive electrode sheet with a diameter of 12 mm using a sheet puncher.

[0079] In a glove box filled with high-purity argon (H2O and O2 were both less than 1 ppm), metallic lithium was used as the counter electrode and reference electrode, and 0.5 mol / L PP 14 Cl / PP 14 TFSI was used as the electrolyte and Celgard 2400 was used as the separator to assemble a CR2032 button cell. The constant current mode was adopted for charging and discharging, with a current density of 10 mA / g and a voltage range of 1.6~3 V.

[0080] Figure 4 The cycling performance obtained by the above test method shows that the first discharge capacity of the BiOCl@polypyrrole composite material is 249 mAh / g, and it still has a capacity of 89 mAh / g after 30 cycles, which is a significant improvement over the pure BiOCl cathode previously reported in "Metal Oxychlorides as Cathode Materials for Chloride Ion Batteries".

[0081] Therefore, the BiOCl@conductive polymer composite material of the present invention can be applied to chloride ion batteries and has broad application prospects.

[0082] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery, characterized in that: The following steps are involved: Step 1, dissolving ammonium persulfate in a NaCl solution to obtain a first mixed solution; Adding BiOCl, polymer monomer and surfactant into NaCl solution, and ultrasonicating and stirring to obtain a second mixed solution; wherein the polymer monomer is pyrrole, and the surfactant is sodium dodecylbenzene sulfonate; Step 2, adding the first mixed solution dropwise into the second mixed solution, and stirring at a temperature of 0-5° C. for more than 24 h to obtain a third mixed solution; Step 3: Filter the third mixed solution, and wash and dry the obtained solid to obtain a BiOCl@conductive polymer composite material.

2. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: The mass ratio of BiOCl to surfactant is 1:(1~2).

3. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: The mass ratio of BiOCl to polymer monomer is 1:(0.05~0.2).

4. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: The ratio of BiOCl to NaCl solution is 1 g:(100~200 mL).

5. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: The molar ratio of the polymer monomer to ammonium persulfate is 1:(1~2).

6. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: The concentration of NaCl solution is 0.1~0.5 mol / L.

7. The method for preparing a conductive polymer-coated bismuth oxychloride positive electrode material for a chloride ion battery according to claim 1, characterized in that: In the step 1, ultrasonic treatment is performed at a temperature of 0-5°C for 1-2 h, followed by stirring for 1-2 h.

8. A conductive polymer-coated bismuth oxychloride positive electrode material prepared according to the method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Bismuth-based photocatalytic MXene membrane material and preparation method thereof

    CN114433226A